The renewed concept of the Batista operation for ischemic cardiomyopathy: maximum ventricular reduction - Gomes,Walter J (2011)
OBJECTIVES: The reconstruction of the left ventricle (LV) is effective in the treatment of ischemic cardiomyopathy with large akinetic or dyskinetic areas. However, late survival outcomes are related to the remnant left ventricular cavity size, thus eliminating intracavitary patch placement provides additional LV reduction. The aim of this study was to analyze the results with left ventricular reconstruction surgery using the concept of maximum ventricular reduction, with systematic patch abolition. METHODS: Seventy-six consecutive patients with ischemic heart disease (age 30-78 years, mean 57.6 ± 10.1), evolving in functional class III and IV underwent surgical ventricular reconstruction with no use of intracavitary patches or Teflon strips for closing the left ventriculotomy. RESULTS: The left ventricular end-systolic diameter decreased from 52.3 ± 5.4 in the preoperative period to 45.2 ± 6.9 mm in the postoperative period. LV ejection fraction increased from 34.2% ± 10.4% to 45.5% ± 9.4%. Associated CABG was performed in 75/76 patients with a mean of 2.4 grafts per patient. The 30-day mortality was 3/76 (3.9%). At an average follow up of 39 months, the majority of the patients (91.4%) remain in functional class I and II. CONCLUSION: The concept of maximizing LV reduction with systematic patchless reconstruction is feasible, safe and effective, the early and late outcomes comparing favorably to previous series reported in the medical literature. Additionally, the concept meets the contemporary pathophysiologic basis of heart failure.